Integrated Practice and Architecture Education: The Evolution of a Pedagogy - Gregory, Alexis; Herrmann, Michele M; Miller, Beth; Moss, Jarrod (ARCC Conference Repository, 2014)
Integrated Practice and Integrated Project Delivery are becoming the norm in architectural practice and therefore must be addressed in architecture education. Architecture programs are also continuously facing pressure from the profession and the collaborative architectural organizations to integrate the profession into education. This has been encouraged through programs such as the various NCARB awards. However, if architecture programs do not take the lead and begin to create programs that address professional education issues, such as integrated practice, the decisions will start to be made for them.This paper is about nascent research on integrated practice being conducted in an architecture program through the design studio. A three-week charette consisting of teams of architecture, interior design, and building construction students has been conducted for the past two years as an experiment in integrated practice and its impact on learning in architecture education. Data was collected through surveys completed by the students through five surveys conducted throughout the three week time period. The first survey was a combination of quantitative data collection in the form of demographic information and qualitative data collection in the form of open-ended questions. The next three surveys were spaced out at certain intervals along the length of the charette and were specifically openended questions. The final survey was a reiteration of the qualitative questions from the original survey to gauge any changes in perceptions and knowledge since the administration of the first survey. This paper will discuss the final results of the data and how that will affect the formation of the integrated practice charette for the next three years of the project. The paper will also propose best practices for using this type of project for a full semester studio, as well as for use by other architecture programs.